Penerapan Model Pembelajaran RADEC Terhadap Peningkatkan Literasi Matematis Siswa Materi Bilangan Bulat - M Farid Nasrulloh; M. Qoyum Zuhriawan; Khusnul Khotimah; Zainudin Azizun Zidan; Rafiqa Rahmayati (Universitas Islam Jember, 2026)
The low student interest in learning is a challenge in mathematics instruction; one potential solution is the RADEC model. Therefore, this study aimed to determine the effect of the RADEC (Read, Answer, Discuss, Explore, Create) learning model on students' mathematical literacy skills regarding the topic of integers. The study employed a quantitative method with a one-group pretest-posttest design involving 36 seventh-grade students at SMP 5 Darul Ulum Jombang. The research instruments consisted of a mathematical literacy test, a teaching module, and RADEC-based student worksheets (LKPD), all of which were validated by experts. The test items underwent a preliminary trial followed by validity and reliability analyses to ensure the selection of valid and reliable items for the pretest and posttest. The Shapiro-Wilk normality test indicated that the data were normally distributed (sig > 0.05). The paired t-test results showed a significance value of 0.000 (p < 0.05), indicating a significant effect. Thus, it can be concluded that the RADEC model is effective in enhancing students' mathematical literacy skills. Keywords:RADEC, Mathematical Literacy, Integers